Community-wide scan identifies fish species associated with coral reef services across the Indo-Pacific. Issue 1883 (25th July 2018) - Maire, Eva; Villéger, Sébastien; Graham, Nicholas A. J.; Hoey, Andrew S.; Cinner, Joshua; Ferse, Sebastian C. A.; Aliaume, Catherine; Booth, David J.; Feary, David A.; Kulbicki, Michel; Sandin, Stuart A.; Vigliola, Laurent; et al.
Abstract : Determining whether many functionally complementary species or only a subset of key species are necessary to maintain ecosystem functioning and services is a critical question in community ecology and biodiversity conservation. Identifying such key species remains challenging, especially in the tropics where many species co-occur and can potentially support the same or different processes. Here, we developed a new community-wide scan (CWS) approach, analogous to the genome-wide scan, to identify fish species that significantly contribute, beyond the socio-environmental and species richness effects, to the biomass and coral cover on Indo-Pacific reefs. We found that only a limited set of species (51 out of approx. 400, approx. 13%), belonging to various functional groups and evolutionary lineages, are strongly and positively associated with fish biomass and live coral cover. Many of these species have not previously been identified as functionally important, and thus may be involved in unknown, yet important, biological mechanisms that help sustain healthy and productive coral reefs. CWS has the potential to reveal species that are key to ecosystem functioning and services and to guide management strategies as well as new experiments to decipher underlying causal ecological processes.